Human mesenchymal stromal cells regulate initial self-renewing divisions of hematopoietic progenitor cells by a β1-integrin-dependent mechanism - Gottschling, Sandra; Saffrich, Rainer; Seckinger, Anja; Krause, Ulf; Horsch, Kerstin; Miesala, Katrin; Ho, Anthony Dick (Stem cells, 2007)
In previous reports, we have demonstrated that only direct cell-cell contact with stromal cells, such as the murine stromal cell line AFT024, was able to alter the cell division kinetics and self-renewing capacity of hematopoietic progenitor cells (HPC). Because β1-integrins were shown to be crucial for the interaction of HPC with the bone marrow microenvironment, we have studied the role of β1-integrins in the regulation of self-renewing cell divisions. For this purpose, we used primary human mesenchymal stromal (MS) cells as in vitro surrogate niche and monitored the division history and subsequent functional fate of individually plated CD34+133+ cells in the absence or presence of an anti-β1-integrin blocking antibody by time-lapse microscopy and subsequent long-term culture-initiating cell (LTC-IC) assays. β1-Integrin-mediated contact with MS cells significantly increased the proportion of asymmetrically dividing cells and led to a substantial increase of LTC-IC. Provided that β1-integrin-mediated contact was available within the first 72 hours, human MS cells were able to recruit HPC into cell cycle and accelerate their division kinetics without loss of stem cell function. Activation of β1-integrins by ligands alone (e.g., fibronectin and vascular cell adhesion molecule-1) was not sufficient to alter the cell division symmetry and promote self-renewal of HPC, thus indicating an indirect effect. These results have provided evidence that primary human MS cells are able to induce self-renewing divisions of HPC by a β1-integrin-dependent mechanism.